Environmental control of the isotopic composition of subfossil coccolith calcite: Are laboratory culture data transferable to the natural environment? - Hermoso, M; Candelier, Y; Browning, T; Minoletti, F (Elsevier, 2015)
Coccoliths contribute significantly to pelagic sediments formed over the last 200 million years, yet their geochemistry has been largely overlooked as a potential record of palaeoenvironmental information. Recently developed techniques have enabled successful extraction of coccolith-dominated sediment fractions. However, the reliability of palaeoenvironmental interpretations that can be drawn from coccolith analyses is still confounded by a poor understanding of the “vital effect” – the physiological component of the isotopic composition of biominerals. Here we demonstrate that oxygen isotope composition in core-top coccoliths is not only set by the temperature and isotopic composition of seawater, but appears to be controlled to first order by the environmental factors regulating algal growth rate. Partial registration of the isotopic signature of assimilated CO2 (with a heavy isotopic composition relative to other dissolved inorganic carbon species) is confirmed to be the dominant mechanism behind the vital effect recorded in the Noelaerhabdaceae coccoliths. Our data point towards a strong role of growth irradiance on expression of the 18O and 13C vital effects, ranging from limited (near equilibrium composition) in low light regimes to 3% offset in oxygen isotopes at higher growth irradiances, such as those found under light-saturated conditions typically imposed in laboratory cultures. This highlights the importance of considering environmental controls when translating oxygen isotope composition of coccoliths into temperature estimates. Furthermore, our calibration suggests that the alkenone-based CO2 palaeobarometer proxy may be refined by combining paired organic/calcite measurements during the Cenozoic.